Comparison of laparoscopic and open approach in the treatment of heterotopic pregnancy following embryo transfer - Chen, Shengfu; Zhu, Yingying; Xie, Meiqing (Frontiers in Surgery, 2022)
Purpose Heterotopic pregnancy (HP) is a rare disease with the coexistence of an intrauterine and ectopic embryos. There is no consensus on the optimal treatment of HP at present. This research aimed to compare the perioperative and pregnancy outcomes of laparoscopic (LA) and open approach (OA) in patients with HP after embryo transfer. Methods Women with HP receiving surgical treatment (LA or OA) were retrospectively recruited in this study between October 2006 and December 2020. The demographic, perioperative and obstetric data were collected and compared between LA and OA group. Results Totally, 86 patients were included in this study. Among these patients, 62 underwent LA and 24 underwent OA. There was an increase in the adoption of LA between the 2006–2012 period and the 2013–2020 period [25% (6/24) vs. 90% (56/62), p < 0.001]. Compared with OA, patients treated by LA had much less blood loss [20 (10–50) vs. 30 (20–50) ml, p = 0.036] and fewer days of hospital stay [5.0 (4.0–7.3) vs. 9.5 (7–15.3) days, p < 0.001], but a relatively higher cost (15,580 ± 3196¥ vs. 11,717 ± 3820¥, p < 0.001). During the laparoscopic procedure, no one needed to be converted to open surgery. However, the rates of first trimester miscarriage, preterm, cesarean section, birth weight, 1- and 5-min Apgar were similar between LA and OA group (all p > 0.05). Conclusions Compared with open approach, laparoscopy was shown to provide a comparable pregnancy outcomes and a better performance on perioperative outcomes in the treatment of HP patients with embryo transfer.